Utility of ELISA screening for the monitoring of abstinence from illegal and legal drugs in hair and urine. Issue 1 (June 2014) - Agius, Ronald; Nadulski, Thomas; Agius, Ronald
<x xml:space="preserve">Abstract</x> Amphetamines, cannabinoids, cocaine, opiates, methadone, and benzodiazepines in authentic hair samples with drug concentrations around the medical and psychological assessment (MPA) guidelines cut‐offs were screened by LUCIO‐direct ELISA kits. Following confirmation of all positive and a significant number of negatively screened samples with gas chromatography‐mass spectrometry (GC‐MS) or liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) methods accredited for forensic purposes. Receiver operating characteristics (ROC) were plotted and the area under the curve (AUC) and overall misclassification rate (OMR) were calculated and compared to those obtained for the same drug classes in urine. While fulfilling the validation criteria of the German forensic guidelines, for almost all screening tests in hair and urine the AUC were greater than 0.8, indicating good to excellent performance. Moreover the AUC calculated for the detection of drugs in hair did not differ significantly to the AUC calculated for the detection of the same drug classes in urine, thus showing a comparable screening performance to the well accepted, previously published application of the same ELISAs for the detection of drugs at unconventionally low cut‐offs in urine. For the first time, the validation of the immunoassay tests for the complete 6‐drug panel MPA profile in hair and urine using a large population of authentic hair and urine samples with drug concentrations around MPA cut‐offs, lower than conventional clinical or workplace drug testing guidelines cut‐offs as well as those suggested by the Society of hair testing (SoHT) is presented. Copyright © 2014 John Wiley & Sons, Ltd.